Multifunctional roles of leader protein of foot-and-mouth disease viruses in suppressing host antiviral responses. (December 2015) - Liu, Yingqi; Zhu, Zixiang; Zhang, Miaotao; Zheng, Haixue
Abstract Foot-and-mouth disease virus (FMDV) leader protein (Lpro ) is a papain-like proteinase, which plays an important role in FMDV pathogenesis. Lpro exists as two forms, Lab and Lb, due to translation being initiated from two different start codons separated by 84 nucleotides. Lpro self-cleaves from the nascent viral polyprotein precursor as the first mature viral protein. In addition to its role as a viral proteinase, Lpro also has the ability to antagonize host antiviral effects. To promote FMDV replication, Lpro can suppress host antiviral responses by three different mechanisms: (1) cleavage of eukaryotic translation initiation factor 4 γ (eIF4G) to shut off host protein synthesis; (2) inhibition of host innate immune responses through restriction of interferon-α/β production; and (3) Lpro can also act as a deubiquitinase and catalyze deubiquitination of innate immune signaling molecules. In the light of recent functional and biochemical findings regarding Lpro, this review introduces the basic properties of Lpro and the mechanisms by which it antagonizes host antiviral responses.